Information Communication and Technology (ICT) Adoption in Asian Countries: An Empirical Evidence of Economic and Socio-Cultural Factors - Wahyu Apriyantopo; Atik Aprianingsih (Binus Business Review, 2020)
The research dealt with factors affected the different Information Communication and Technology (ICT) adoption rate among Asian countries. The primary purpose was to examine the impact of national wealth and culture on the behavioral adoption of ICT empirically among selected countries in Asia. Data were collected from the World Bank, World Economic Forum, and Hofstede’s cultural dimension index. Statistical correlation and multiple regression were utilized to analyze the dataset, such as Gross Domestic Product (GDP) as a proxy for national wealth and Hofstede’s cultural dimension as a proxy for culture. The result shows a significant relationship between GDP per capita and uncertainty avoidance on the national ICT adoption index. This finding contributes to improving the acknowledgment of the GDP and national culture as the antecedent of ICT adoption in the global field. Practically, the research updates the previous similar ones and proposes further empirical research to extend the scope of analysis.